Variability by yield and grain quality of winter wheat varieties collection - Nazarenko, M. M.; Horshchar , V. I. (Scientific Progress & Innovations, 2019)
The purpose of the article was to identify the variability limits of the main yield and grain quality parameters of 14 soft winter wheat varieties under the conditions of the Northern Steppe of Ukraine. Methods of research are defining yield and parameters of its structure, laboratory analysis of moisture, protein and gluten percentage content in field conditions. The research results. Data about two possibilities of high grain yield formation under our conditions at the expense of higher productive tillering capacity or higher grain productivity of the main spike have been obtained. During the first process grain of high quality (sufficient content of protein and gluten) has been received too. As to the yield and grain quality in complex, the varieties Kalancha and Zoloto Ukrainy, as to the yield, the variety Nyva Odeska, as to the content of protein and gluten the varieties Vinok Podillia, Polianka, Zelenyi Hai (from which the latter two were not inferior concerning the standard by grain productivity), as to the gluten content the variety Balaton have been selected. The elements of scientific novelty. Further development of the idea about the possibilities of forming basic agronomic-valuable signs has been discovered. New valuable donors of these signs for breeding research have been revealed. Practical value. The ways of yield formation and its key characteristics, and also the quality of soft winter wheat genotypes have been established. Key words: winter wheat, yield, variety, grain quality. Statement of the problem. The analysis of separate genotypes, as well as procedures of selecting promising genotypes, are becoming more and more localized and require more careful and deep investigation under the specific conditions of a particular region. First of all, it refers to such signs as quality, the presence of certain nutritionally valuable components, genetically stipulated resistance to diseases and pests to eliminate the pesticide loading. More and more attention is being paid not to increasing grain yield as such, but to reducing the cost of cultivation technology due to variety properties, reducing the anthropogenic loading, obtaining more valuable products. Considering the possibility of raising these parameters, it can even lead to reducing the yields (but not quality). The purpose of the research was to establish the limits of main yield and grain quality parameters’ variability of 14 soft winter wheat varieties under the conditions of the Northern Steppe of Ukraine and demonstrate higher adaptive genotypes by individual signs and in the complex of economically-valuable signs. The research task was to analyze yields and their structure of 14 soft winter wheat varieties, as compared with the standard, investigate quality parameters, establish the variability limits of these signs, identify better samples according to separate properties and the complex of such properties under the regional conditions. Materials and methods of research. Experiments were carried out on the experimental fields of Dnipro State Agrarian and Economic University. 14 winter wheat varieties have been analyzed. Podolianka was used as the standard variety. The evaluation of the total grain yield per area was calculated from 2016 to 2018. The testing of winter wheat varieties was set up in three replications and on the area of 1.5 m2. Data on yield structure components were taken from 0.25 randomly selected plots of each variety. Protein, gluten and water content of the samples were measured by Near-infrared Reflectance Spectroscopy (Spektran-IT). Triplicate data of each sample were averaged. Mathematical processing of the results was conducted by the method of variance analysis, student's t-test, and cluster analyses. The research results. By the parameter of the number of productive stems per m2 such varieties as Vinok Podillia and Zoloto Ukrainy exceeded the standard, as to the number of grains on the main spike it was Balaton, that exeeded. The weight of grain on the main spike in Talisman, Pochaina, Zelenyi Hai varieties was higher, the weight of grain per m2 in Kalancha and Zoloto Ukrainy varieties exceeded the standard. The yield was higher regarding higher tillering capacity, rather than the increase in the productivity of the main spike for the varieties Zoloto Ukrainy and Kalancha, but for Nyva Odeska variety, usually, the reverse mechanism of yield formation is characteristic not at the expense of a greater number of productive spikes, but because of higher grain productivity of the main spike. High yield is characteristic for such varieties as Kalancha, Zoloto Ukrainy, Nyva Odeska (this index is higher than the standard). Concerning the percentage of grain in the total yield, many varieties have been identified, which indicates their predominantly intensive nature. As a result of cluster analysis, the varieties were divided into three groups. The first group included the varieties that constantly have higher yields than the standard (Kalancha, Zoloto Ukrainy, Nyva Odeska). The second group included the varieties with yields at the level of Podolianka standard (Balaton, Borovytsia, Talisman, Polianka, Pochaina, Zelenyi Hai). The third group included the varieties Vinok Podillia, Zdoba Kyivska, Nasnaha, Vykhovanka Odeska, Nastia, which showed significantly lower yields during all the years. By the parameter of protein content in grain we can distinguish such varieties as Vinok Podillia, Polianka, Zelenyi Hai. However, Kalancha and Zoloto Ukrainy varieties have the quality at the level of Podolianka and requirements for strong wheat. The variety Kalancha has higher protein content than the standard. Conclusion. Thus, concerning the set of grain quality signs and yields, the varieties Kalancha and Zoloto Ukrainy were distinguished as the most suitable for our region; concerning the yield it was Nyva Odeska variety, but it had significantly worse quality indices. As to the content of protein and gluten such varieties as Vinok Podillia, Polianka, Zelenyi Hai were distinguished; by the content of gluten Balaton variety was chosen. Under our conditions, high grain yield can be formed either at the expense of high productive tillering capacity (Kalancha and Zoloto Ukrainy), or due to high grain productivity of the main spike (Nyva Odeska). No other possibilities were detected. Depending on this, the key parameters were either the number of productive stems per m2 and the weight of grain per m2, or the weight of grain from the main spike.